DEVELOPMENT OF REALISTIC MATHEMATICAL LEARNING DEVELOPMENT OF STATISTICS MATERIAL IN CLASS IX SMP NEGERI 3 PAREPARE - Andi Rusdi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
The purpose of this research is to develop learning tools in mathematics learning using realistic mathematics learning in Class IX SMP, with this tool is expected to change the paradigm of learning "centered on teacher" to "student-centered". This research is a research development (Reasearch and Development) which uses qualitative descriptive method, and through development experiments referring to Four-D Thiagarajan model (1994), namely difine, design, develop, and disseminate. The results of the study show that: (1) learning tools developed meet the criteria of valid, practical and effective, (2) the ability of teachers in managing learning "good" category, (3) student activity in effective category, (4) And "positive" teachers, (5) average achievement of learning outcome 73,33 with classical completeness level 87,50%.